# Hyperoperation sequence #

This file defines the Hyperoperation sequence. hyperoperation 0 m k = k + 1 hyperoperation 1 m k = m + k hyperoperation 2 m k = m * k hyperoperation 3 m k = m ^ k hyperoperation (n + 3) m 0 = 1 hyperoperation (n + 1) m (k + 1) = hyperoperation n m (hyperoperation (n + 1) m k)

## Tags #

hyperoperation

def hyperoperation :

Implementation of the hyperoperation sequence where hyperoperation n m k is the nth hyperoperation between m and k.

Equations
Instances For
@[simp]
theorem hyperoperation_zero (m : ) :
theorem hyperoperation_recursion (n : ) (m : ) (k : ) :
hyperoperation (n + 1) m (k + 1) = hyperoperation n m (hyperoperation (n + 1) m k)
@[simp]
theorem hyperoperation_one :
= fun (x x_1 : ) => x + x_1
@[simp]
theorem hyperoperation_two :
= fun (x x_1 : ) => x * x_1
@[simp]
theorem hyperoperation_three :
= fun (x x_1 : ) => x ^ x_1
theorem hyperoperation_ge_two_eq_self (n : ) (m : ) :
hyperoperation (n + 2) m 1 = m
theorem hyperoperation_ge_three_one (n : ) (k : ) :
hyperoperation (n + 3) 1 k = 1
theorem hyperoperation_ge_four_zero (n : ) (k : ) :
hyperoperation (n + 4) 0 k = if Even k then 1 else 0